Some Comments on Assessment in U.S. Education - Stake, Robert (Education Policy Analysis Archives, 1998)
We do not know much about what assessment has accomplished but we know it has not brought about the reform of American Education. The costs and benefits of large scale mandated achievement testing are too complex to be persuasively reported. Therefore, educational policy needs to be based more on deliberated interpretations of assessment, experience, and ideology. Evaluation of assessment consequences, however inconclusive, has an important role to play in the deliberations.